Emerging Antibiotic Resistance and Limited Therapeutic Options for Common Infections in Sylhet, Bangladesh - Benzamin, Md; Chakroborty, Pranto; Mahmud, Shawmik; Das, Kamalesh; Dhar, Prima; Sharma, Nilanjana; Roy, Debajani; Ahmad, Rayhan; Zaman, Tanvir Uz; Khatoon, Mohsina (Bangladesh Medical Journal, 2025)
Rising antimicrobial resistance (AMR) substantially undermines infection management worldwide. In Bangladesh, regional variations in resistance hinder empirical therapy. This study characterizes local AMR patterns among clinical isolates in a private tertiary level hospital in Sylhet, Bangladesh. We retrospectively reviewed culture and sensitivity records from July 2023 to February 2024 at Mount Adora Hospital. Specimens included urine, sputum, blood, and wound swabs. Identification and antibiotic sensitivity testing followed Clinical and Laboratory Standards Institute guidelines. Descriptive statistics summarized pathogen distribution and resistance rates. Of 1,360 culture-positive specimens, urine dominated (57.6%), followed by sputum (24.1%), blood (15.9%), and wound swabs (2.4%). Escherichia coli (54.5%) and Klebsiella spp. (20.4%) led urinary isolates; Staphylococcus aureus predominated blood cultures (70.8%); Streptococcus spp. (36.6%) and Klebsiella spp. (32.9%) were common in sputum; wound swabs chiefly yielded S. aureus (42.4%). High resistance in urine isolates was noted for azithromycin (80.9%), cefixime (78.3%), and nalidixic acid (79.1%); carbapenems retained >80% activity. Bloodstream isolates showed >75% resistance to cefixime and ceftazidime but remained >80% sensitive to imipenem and amikacin. Sputum and wound pathogens exhibited similar resistance trends to first-line agents, with tigecycline and carbapenems preserving efficacy. Common antibiotics demonstrate alarming resistance rates, whereas reserve antibiotic particularly carbapenems and tigecycline remain reliable. Updated, region-specific antibiotic guidelines and stewardship interventions are immediately needed. Bangladesh Med J. 2024 Sept; 53(3): 23-30